The Authenticity Of English Language Assessment For The Twelfth Grade Students Of Smk Negeri 4 Surakarta In Academic Year Of 2015/2016 - HIDAYATI, NURUL (2016)
This research aims at finding some empirical facts about what types of assessments are used by the English teachers in assessing English Language, how is the authenticity of the assessment used by the teacher, how do teachers use the assessment to score the students' learning outcome and what problems are encountered by the teachers in applying authentic assessment for English language. The research method used is qualitative research, and it focuses on the authenticity of English assessment used by the teacher. The data was collected by using observation which was done in the classroom during the assessment process, interview and content-analysis. Observations were conducted to get the data about students' activity during the process of assessment. Interviews were conducted to get the data about the implementation of authentic assessment and the problems encountered by teachers in the implementation. The document study was conducted to get the data about the assessment documents used by the teachers. The findings of this research are firstly the teacher used three types of assessment : (a) Formative Test which covers affective-cognitive-psychomotor aspects. In assessing affective aspect teachers used observation, in assessing cognitive aspect teachers used written test and in assessing psychomotoric aspect teacher used performance test, product and portfolio. (b) Mid Term Test (c) Semester Test. Secondly, the Formative Test used by the teachers has high level of authenticity, while the Mid Term Test and Semester Test had very low authenticity. Thirdly, the scoring system used was the Criterion Reference Test which refers to Minimum Mastery Criteria. Forthly, there were at least four problems in applying authentic assessment : (a) the teacher felt overburdened with too many assessment formats (b) the inconsistency in educational regulation cause confusion for school practitioner (c) insufficient learning facilities caused in the assessment not effective (d) insufficient IT system needed to be improved. The school had been doing efforts to overcome the problems. Keyword : authenticity, assessment, and authentic assessment